Sustainability reports disclosures: Siapakah stakeholder yang paling penting? - Binti Shofiatul Jannah; Hans Wakhida Rakhmatullah; Yohan Bakhtiar (Universitas Pamulang, 2021)
This study aims to analyze the most important stakeholders in Indonesian companies. One of the main reporting principles in GRI 101 is stakeholder inclusiveness. Content analysis was used to identify stakeholders in 38 companies that participated in the 2017 Sustainability Reporting Awards. The first step taken is coding the stakeholders. The next step is to record the symbols and interpret the results according to the typology of stakeholder Mitchell et al (1997). The findings of the study show that shareholders and government are the most important stakeholders, regardless of industry differences in the sample. AbstrakPenelitian ini bertujuan untuk menganalisis stakeholder yang paling penting di perusahaan Indonesia. Salah satu prinsip pelaporan utama dalam GRI 101 adalah inklusivitas stakeholder. Analisis konten digunakan untuk mengidentifikasi stakeholder di 38 perusahaan yang mengikuti Sustainability Reporting Awards 2017. Langkah pertama yang dilakukan adalah melakukan coding terhadap stakeholder. Langkah selanjutnya adalah merekam simbol dan menafsirkan hasilnya sesuai kerangka typology stakeholder Mitchell et al (1997). Temuan penelitian menunjukkan bahwa pemegang saham dan pemerintah menjadi pemangku kepentingan yang paling penting, terlepas dari perbedaan industri dalam sampel.